New urbanism, crime and the suburbs: a review of the evidence - Cozens, Paul (Taylor and Francis (Routledge), 2008)
Sustainability now influences government policy in the UK, Australia and USA and planning policy currently advocates high density, mixed-use residential developments in 'walkable', permeable neighbourhoods, close to public transport, employment and amenities. This clearly demonstrates the growing popularity, influence and application of New Urbanist ideas.This paper reviews the criminological research relating to New Urbanism associated with the three key issues of permeability, rear laneway car parking and mixed-use development. These key issues are discussed from an environmental criminology perspective and challenge New Urbanist assumptions concerning crime. The paper proposes that crime prevention through environmental design (CPTED) and its crime risk assessment model represents a valuable tool for New Urbanists to utilise to reduce opportunities for crime and tackle fear of crime in the community. Recommendations for future research and collaboration are discussed.